2019
DOI: 10.1103/physreva.100.010502
|View full text |Cite
|
Sign up to set email alerts
|

QED radiative corrections to the P1/22P3/22

Abstract: Ab initio calculations of QED radiative corrections to the 2 P 1/2 -2 P 3/2 fine-structure transition energy are performed for selected F-like ions. These calculations are nonperturbative in αZ and include all first-order and many-electron second-order effects in α. When compared to approximate QED computations, a notable discrepancy is found especially for F-like uranium for which the predicted self-energy contributions even differ in sign. Moreover, all deviations between theory and experiment for the 2 P 1/… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 60 publications
(63 reference statements)
9
25
1
Order By: Relevance
“…Here, we note that the screened self-energy formulas perfectly agree with the ones of Ref. [34], where they were obtained by considering the diagrams depicted in Fig. 3 directly.…”
Section: Screened Radiative Correctionssupporting
confidence: 85%
See 2 more Smart Citations
“…Here, we note that the screened self-energy formulas perfectly agree with the ones of Ref. [34], where they were obtained by considering the diagrams depicted in Fig. 3 directly.…”
Section: Screened Radiative Correctionssupporting
confidence: 85%
“…First, in Refs. [33][34][35] it was demonstrated that highly accurate theoretical predictions are possible in such atoms, and thus accurate tests of the QED effects become feasible. The reason for this is a drastic reduction of the correlations due to Layzer quenching effects [54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expressions above provide all contributions to the screened self-energy and vacuum polarization. Here, we note that the screened self-energy formulas perfectly agree with the ones of Reference [45], where they were obtained by considering the diagrams depicted in Figure 3 directly.…”
Section: Screened Radiative Correctionssupporting
confidence: 85%
“…In order to illustrate the developed method, the first-(one-photon exchange) and secondorder (screened QED and two-photon exchange) many-electron QED diagrams are derived for the case of single-vacancy atoms. Such an example is chosen due to the fact that twophoton-exchange correction is still uncalculated for fluorine-like ions [44][45][46] as well as due to recent experimental efforts for such systems [47,48].…”
Section: Introductionmentioning
confidence: 99%